THE EFFECTIVENESS OF THE USABILITY OF RESEARCHGATE AS A MEDIA IN HELPING THE INDEXING OF SCIENTIFIC WORK PUBLICATIONS - Ahmad Taufik; Rouly Doharma; Agus Budiyantara; T. Husain Husain; Asrul Sani (Green Publisher, 2022)
In the information era of borderless internet development and massive unlimited data access, especially in science and technology, one of which requires researchers and lecturers to rectify innovation, the quality, and quantity of research in Indonesia. This research examines the importance of empirically proving the success of the ResearchGate social media platform derived from Usability as a medium for indexing scientific paper publications that are needed for academic researchers these days. The following study is causality type research with a quantitative approach. The final sampling only involved 70 respondents who fulfilled the proviso's active ResearchGate account of at least one month. This research assesses Usability using a statistical inferential, i.e., linear regression analysis. These results concluded that generally, determinant Usability consists of Learnability, Memorability, Efficiency, and Errors, which have no implication partially, but Satisfaction has implication toward Usability. Still, Usability has substance simultaneously with a strong enough contribution score of 63.7 percent in ability ResearchGate indexing scientific paper publication